Colonialism and religion - Chidester, David 1952- (2013)
As critical research on religion, the study of colonialism and religion directs attention to religious creativity within the asymmetrical power relations of contact zones, intercultural relations, and diasporic circulations. Taking the imperial ceremony of the 2012 London Olympics as a point of departure, this article recalls how the drama of the colonizing Prospero and the colonized Caliban has been a template for analyzing religion under colonial conditions. Like Shakespeare’s enchanted isle, colonizing and colonized religion have been shaped by oceans, with the Mediterranean, Atlantic, Indian, and Pacific worlds emerging as crucial units of analysis. As a contribution to a symposium on critical approaches to the study of religion, this article indicates some of the important landmarks, sea changes, and analytical possibilities in the study of colonialism and religion.
Keywords: Caliban; contact zones; Hybridity